The Method of Ethics-as-Process: Embracing Ambivalence in Research on Childhood and Deportability - Lind, Jacob (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2017)
Even though ethics should not be instrumentalised, discussing ethical issues with participants and gatekeepers can nevertheless lead to new knowledge. Through examples from ethnographic research among children and families fearing deportation in Birmingham, UK and Malmö, Sweden, this article reflects upon how an ethics-as-process approach can become part of the knowledge production itself in sensitive and politicised research contexts. This is a result of the ambivalent nature of ethnographic research with vulnerable groups and the article therefore encourages researchers to embrace the ambivalences of co-constructing the field, working with gatekeepers and establishing trust and consent to enable a more transparent and reflexive knowledge production. In conclusion, it is suggested that the increased politicisation of the issue of child and family migration will make necessary that researchers, who wish to embrace this ambivalence, align with the self-expressed struggle of participants to enable high-quality participatory research among these groups.
Keywords: ethics-as-process; ethnography; deportability; childhood; ambivalence